A Personal Branding and Adolescent Self-Identity: Understanding the Role of First Accounts and Second Accounts in the Digital Context - Lia Yunikawati; Phaulina, Cindy; Fitria P., Della; Safira Prima, Yuliani (Prodi Sosiologi Agama, 2024)
Information systems. The advancing information technology also influences a person's lifestyle. One's lifestyle on social media and in the real world, as well as the social environment, play a significant role in shaping one's identity. This is also true for teenagers in Ponorogo. A positive social environment will create a positive personality, and vice versa. Peer influence, including friends and playmates, also shapes an individual's lifestyle. This is not much different from what happens to teenagers in SMA Negeri 2 Ponorogo. Social interaction factors can be a motive for teenagers to create a certain image of themselves. Some teenagers are even willing to change their original self-image on social media to be accepted within a friendship circle, using both first and second accounts. Therefore, this research needs to be conducted to understand the role of first and second accounts in strengthening teenagers' self-identity through personal branding built in the digital world. The research methods used in this study are qualitative and quantitative. Data is collected through questionnaires and explored further through interviews. The research findings show that teenagers from SMA Negeri 2 Ponorogo have two categorizations in their use of social media. Firstly, the first account is used as a means to build personal branding, taking into consideration others' perception and expression. Secondly, the second account is utilized to build a free personal branding that influences teenagers' self-identity in the digital world.